A flexible solid-state energy storage battery embedded with magnetic conductive filler
Patent Information
- Application Number
- CN202611210585.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这种追求单一方向高导电性的设计思路存在明显局限:当弯折方向垂直于取向方向时,导电通路易被拉伸断裂,导致电阻急剧上升;而当弯折方向平行于取向方向时,导电通路虽受压缩,但另一垂直方向并无有效导电冗余
1、区别于现有技术中追求单一方向最优导电性的各向异性导电设计,本发明突破了该技术偏见,通过牺牲部分单方向导电性,构建双取向交错结构,使电解质层在面内至少两个不同方向上均具有有效导电通路,显著提升了多方向弯折下的导电稳定性;
Smart Images

Figure CN123018081A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, and more specifically to a flexible solid-state energy storage battery with embedded magnetic conductive filler. Background Technology
[0002] With the rapid development of wearable electronic devices, flexible displays, and implantable medical devices, the demand for energy storage devices that combine high energy density and excellent mechanical flexibility is becoming increasingly urgent. Traditional liquid lithium-ion batteries, due to safety hazards such as electrolyte leakage and separator puncture, and their rigid structure's inability to adapt to complex deformations, can no longer meet the application requirements of flexible electronics. Solid-state batteries, which use solid electrolytes instead of liquid electrolytes, fundamentally eliminate the risk of leakage, while also offering a wider operating temperature range and higher energy density, and are considered an important development direction for next-generation flexible energy storage technology.
[0003] However, existing solid-state flexible batteries still face significant challenges. On the one hand, solid electrolytes are prone to cracking during bending, leading to interruptions in ion transport channels and deterioration of interfacial contact. On the other hand, conductive fillers introduced to improve flexibility are susceptible to conductive network breakage under repeated deformation, resulting in a sharp increase in internal resistance and rapid capacity decay. Although researchers have attempted to improve flexibility and conductivity by adding conductive fillers such as carbon nanotubes and graphene or by using gel electrolytes, these approaches are mostly static structural designs, making it difficult to balance long-term cycle stability and electrochemical performance.
[0004] Magnetic field alignment technology has been used to prepare anisotropic conductive composite materials. Existing techniques typically employ a single magnetic field treatment to orient the conductive filler along a specific direction to achieve optimal conductivity in that direction. However, this design approach, which pursues high conductivity in a single direction, has significant limitations: when the bending direction is perpendicular to the alignment direction, the conductive path is easily stretched and broken, leading to a sharp increase in resistance; while when the bending direction is parallel to the alignment direction, although the conductive path is compressed, there is no effective conductive redundancy in the other perpendicular direction. Therefore, the reliability of existing single-orientation structures under complex deformations in multiple directions is insufficient.
[0005] Furthermore, there are no existing reports on the synergistic construction of modulus gradient and dual-orientation magnetic field alignment within the same electrolyte layer via patterned photopolymerization to address the technical problem of conductive network breakage in flexible solid-state batteries under multi-directional bending. Therefore, developing a solid-state flexible energy storage battery capable of maintaining the integrity of its conductive network under multi-directional bending remains a pressing technical challenge in this field. Summary of the Invention
[0006] The purpose of this invention is to provide a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler. By constructing a spatially non-uniform solidification structure and a dual-oriented interlaced conductive network, the technical defects of existing flexible solid-state batteries, such as easy breakage of the conductive network and rapid performance degradation during repeated bending, are overcome.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A bendable solid-state flexible energy storage battery with embedded magnetic conductive filler includes a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive and negative electrodes; the solid electrolyte layer contains embedded magnetic conductive filler, which forms a conductive network in the solid electrolyte layer; the solid electrolyte layer has alternating high-modulus regions and low-modulus regions, the ratio of the elastic modulus of the high-modulus region to the low-modulus region being 2:1 to 10:1; the magnetic conductive filler in the high-modulus region is arranged in a first orientation, and the magnetic conductive filler in the low-modulus region is arranged in a second orientation, the first orientation and the second orientation forming an angle of 50° to 120°.
[0008] Preferably, the magnetic conductive filler includes a core-shell structure, which includes a magnetic core and a conductive shell covering the surface of the magnetic core; the coercivity of the magnetic core is 50 Oe to 500 Oe, and the remanence is 5 emu / g to 20 emu / g.
[0009] Preferably, in the high modulus region, the mass fraction of the magnetic conductive filler is higher than that in the low modulus region, and the total mass fraction of the magnetic conductive filler in the solid electrolyte layer is 8% to 25%, and the spacing between adjacent high modulus regions is 50 μm to 500 μm.
[0010] Furthermore, selective sedimentation or zoned coating processes can be used to reduce the mass fraction of magnetic conductive filler in the low-modulus region to be lower than that in the high-modulus region. For example, the mass fraction of magnetic conductive filler in the low-modulus region is 1% to 5%, while that in the high-modulus region is 8-25%, thereby further reducing the elastic modulus of the low-modulus region.
[0011] Preferably, the solid electrolyte layer includes a first sublayer near the positive electrode and a second sublayer near the negative electrode; the high modulus region and the low modulus region in the first sublayer are arranged in an alternating stripe pattern, and the stripes extend along the first in-plane direction; the high modulus region and the low modulus region in the second sublayer are arranged in an alternating stripe pattern, and the stripes extend along the second in-plane direction, and the first in-plane direction and the second in-plane direction are perpendicular to each other.
[0012] Preferably, the solid electrolyte layer further includes a non-magnetic ion conductor filler, which is interspersed with the magnetic conductive filler to form a structure in which continuous ion transport channels and an in-plane electronic conductive network are interspersed; wherein, the mass ratio of the non-magnetic ion conductor filler to the magnetic conductive filler is 1:3 to 3:1, and the ionic conductivity of the solid electrolyte layer is 1.5 to 5 times higher than that of the control sample without the non-magnetic ion conductor filler; the in-plane electronic conductive network is covered and isolated by the solid electrolyte matrix and is discontinuous in the battery thickness direction.
[0013] The mass ratio range of 1:3 to 3:1 is based on the following: When the mass ratio is lower than 1:3 (i.e., the content of non-magnetic ionic conductor filler is too low), the non-magnetic ionic conductor filler cannot form continuous ion conduction channels in the network gaps of the magnetic conductive filler, resulting in limited improvement in ionic conductivity (usually less than 1.5 times), making it difficult to exert the synergistic effect of "ion bridges"; when the mass ratio is higher than 3:1 (i.e., the content of non-magnetic ionic conductor filler is too high), excessive non-magnetic ionic conductor particles will dilute the effective concentration of the magnetic conductive filler in the slurry, leading to a decrease in magnetic field orientation efficiency, and the non-magnetic ionic conductor particles may agglomerate and compete with the magnetic filler, destroying the regularity of the dual-orientation staggered structure. Example 3 uses a mass ratio of 1:1, at which point the two fillers are most evenly distributed, the ionic conductivity is improved by 2.4 times, and there is no negative impact on the magnetic field orientation degree and bending durability. Therefore, 1:3 to 3:1 is the preferred ratio range for achieving a structure with continuous ion transport channels and an in-plane electronic conductive network staggered distribution.
[0014] The present invention also provides a method for preparing the above-mentioned battery, comprising the following steps: dispersing magnetic conductive filler in a solid electrolyte precursor solution containing photocurable monomers to obtain a composite slurry; coating the composite slurry onto the surface of a flexible substrate, applying a first steady magnetic field with a magnetic field strength of 0.1T to 2T during the coating process, causing the magnetic conductive filler to be oriented along a first direction; under the condition of maintaining the first magnetic field, performing patterned ultraviolet curing on the coating layer, wherein the patterned curing adopts a periodic stripe pattern with a stripe width of 50μm to 500μm and a stripe spacing of 100μm to 1000μm, so that a curing gradient field with alternating cured and uncured areas is formed in the coating layer; removing the first magnetic field and applying a second magnetic field, wherein the direction of the second magnetic field is at an angle of 50° to 120° with the first direction, and the magnetic field strength is... H 2 and the strength of the first magnetic field H The ratio of 1 is H 2 / H I = 0.3 to 0.7, causing the magnetic conductive filler in the uncured area to undergo secondary orientation, forming an interleaved orientation structure; the coating layer after secondary orientation is cured as a whole to obtain the solid electrolyte layer.
[0015] Preferably, the ratio of the elastic modulus of the cured region to that of the uncured region is 2:1 to 10:1.
[0016] Preferably, the photocurable monomer includes an ionic liquid monomer containing double bonds, which forms the ion transport matrix of the solid electrolyte layer after photocuring.
[0017] Preferably, the application time of the second magnetic field is 0.2 to 0.5 times that of the application time of the first magnetic field, and the temperature of the overall curing is lower than that of the patterned photocuring.
[0018] The mechanism of action of this invention is as follows: After patterned photocuring, the solid electrolyte layer forms a spatially non-uniform structure with alternating high-modulus regions (i.e., cured regions) and low-modulus regions (i.e., uncured regions formed after overall curing). When the battery is bent, the low-modulus regions, due to their lower elastic modulus, preferentially undergo shear deformation to absorb bending energy, while the high-modulus regions maintain structural integrity to preserve the ion transport framework and the main framework of the conductive network. Since the magnetic conductive fillers in the high-modulus and low-modulus regions are arranged along a first orientation and a second orientation, respectively, with the two orientations at an angle of 50° to 120°, when bending along one orientation causes stretching and partial contact degradation of the conductive pathway in that direction, the conductive pathway in the other orientation maintains or improves the contact state due to the difference in matrix deformation modes, forming complementary conductive paths, thereby suppressing a sharp increase in overall resistance.
[0019] It should be noted that although the magnetic conductive filler forms a conductive path in the solid electrolyte layer, this conductive network is fully encapsulated and isolated by the ionic liquid polymer matrix, and the non-magnetic ionic conductor filler (such as LATP) fills the gaps between the conductive fillers, effectively blocking the through-transmission of electrons in the thickness direction of the battery. Therefore, it will not cause an internal short circuit between the positive and negative electrodes. The above structure maintains the interfacial electrical contact stability during bending while preserving the necessary electronic insulation of the electrolyte layer.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Unlike the anisotropic conductive design in the prior art that pursues optimal conductivity in a single direction, this invention breaks through the bias of this technology. By sacrificing some unidirectional conductivity, a dual-orientation staggered structure is constructed, so that the electrolyte layer has an effective conductive path in at least two different directions in the plane, which significantly improves the conductivity stability under multi-directional bending. 2. Unlike the static conductive network design in the prior art where conductive fillers are uniformly dispersed or have a single orientation, this invention uses a synergistic process of patterned photocuring and two-step magnetic field orientation to simultaneously construct a spatial non-uniform curing structure with alternating orientations of high-modulus and low-modulus regions within the same electrolyte layer. When bent, this structure disperses stress through the synergistic effect of "rigid skeleton-flexible hinge" and maintains the integrity of the conductive network through the complementarity of multi-directional conductive pathways. 3. Unlike existing single-magnetic field orientation processes, this invention adopts a synergistic strategy of patterned ultraviolet curing combined with two magnetic field orientations. First, a high field strength is used to lock the primary orientation of the high modulus region, and then a low field strength is used to induce the secondary orientation of the low modulus region, thus constructing a dual-orientation staggered structure. This allows the electrolyte layer to exhibit differentiated mechanical response and conductivity characteristics in the in-plane and thickness directions, breaking through the limitation of strong direction dependence of single-orientation structures. 4. Unlike existing homogeneous solid electrolyte layers, this invention precisely controls the patterned photocuring parameters to make the ratio of elastic modulus of the high modulus region to the low modulus region 2:1 to 10:1, with clear deformation functional zones. Among them, the high modulus region maintains structural integrity to maintain the ion transport framework, while the low modulus region undergoes controllable shear deformation to absorb bending energy, avoiding the risk of overall brittle cracking of the homogeneous structure when bending. 5. Unlike the existing parallel stacked single-orientation structure, the first sub-layer and the second sub-layer of this invention adopt an orthogonal arrangement design, so that each sub-layer bears stress components in different directions when bent, which effectively suppresses interlayer stress concentration and delamination, and improves the overall bending durability of the battery. 6. Unlike existing physically mixed ion-electron dual continuous networks, the non-magnetic ion conductor filler and magnetic conductive filler of the present invention are interspersed to form a structure in which ion continuous transport channels and in-plane electronic conductive networks are interspersed. The ionic conductivity of the solid electrolyte layer is 1.5 to 5 times higher than that of the control sample without the non-magnetic ion conductor filler. It maintains a synergistic improvement in high ion transport efficiency and mechanical durability during bending. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the cross-sectional structure of the bendable solid flexible energy storage battery with embedded magnetic conductive filler of the present invention. Figure 2 This is a schematic diagram of the fabrication process of the bendable solid-state flexible energy storage battery of the present invention; Reference numerals: 1. Positive electrode; 2. Solid electrolyte layer; 3. Negative electrode; 4. Magnetic conductive filler. Detailed Implementation
[0022] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the present invention, they are protected by patent law.
[0023] I. Implementation Section.
[0024] Example 1
[0025] Preparation of S1.1 Core-shell structured magnetic conductive filler: Fe3O4 nanoparticles with a particle size of 50 nm were dispersed in anhydrous ethanol and sonicated at 300 W for 30 minutes to achieve uniform dispersion, resulting in a magnetic core suspension with a concentration of 10 mg / mL. Multi-walled carbon nanotubes (outer diameter 10-20 nm, length 5-15 μm, purity >95%) were added to the suspension at a mass ratio of 1:2 to Fe3O4. The mixture was stirred at 600 rpm for 12 hours in a 60°C water bath to allow the carbon nanotubes to coat the Fe3O4 surface through π-π interactions and van der Waals forces, forming a core-shell structured magnetic conductive filler. After centrifugation and washing (8000 rpm, 10 minutes, three washes with ethanol), and vacuum drying at 60°C for 12 hours, the magnetic properties were tested at room temperature using a vibrating sample magnetometer (VSM, Lake Shore 7407). The filler showed a coercivity of 120 Oe, a remanence of 12 emu / g, and a saturation magnetization of 45 emu / g.
[0026] The morphology of the filler was observed using transmission electron microscopy (TEM, JEOL JEM-2100F, accelerating voltage 200kV). The results showed that the Fe3O4 nanoparticles were uniformly coated with a carbon nanotube network, forming a distinct core-shell structure, with a carbon nanotube coating thickness of approximately 5-10 nm. The dispersed particle size of the filler in ethanol was measured using a laser particle size analyzer (Malvern Mastersizer 3000), with a D50 of 120 nm, indicating that the filler has good dispersion stability in solution.
[0027] The selection criteria for the S1.2 magnetic core parameter range are as follows: The range of coercivity from 50 Oe to 500 Oe and remanence from 5 emu / g to 20 emu / g is based on the following: (1) When the coercivity is less than 50 Oe, the magnetic core is difficult to maintain the magnetic moment stability required for directional alignment after the external magnetic field is removed, which leads to relaxation of the filler after the first orientation in the subsequent process and a decrease in orientation degree. (2) When the coercivity is higher than 500 Oe, the filler is difficult to be effectively oriented by conventional electromagnets (field strength < 2T) during the preparation process, and the excessively high coercivity means that the magnetic moment of the filler is difficult to reverse, resulting in insufficient responsiveness in the secondary orientation step. (3) When the remanence is less than 5 emu / g, the magnetic responsiveness of the filler in the slurry is insufficient, the orientation efficiency is low, and it is necessary to extend the magnetic field action time or increase the magnetic field strength, which is not conducive to industrial production. (4) When the remanence is higher than 20 emu / g, the magnetic dipole interaction between fillers is too strong, which can easily lead to magnetoagglomeration in the slurry, destroying the uniformity of the conductive network. Furthermore, high remanence fillers may undergo long-term relaxation due to magnetic interaction after curing, resulting in unstable orientation structure.
[0028] Preparation of S1.3 composite slurry The ionic liquid monomer 1-vinyl-3-butylimidazolium bis(trifluoromethanesulfonyl)imide salt ([VBIM][TFSI], double bond density 4 mmol / g, viscosity 120 mPa·s at 25 °C) containing double bonds was mixed with the photoinitiator 2-hydroxy-2-methylphenylacetone (HMPP, Irgacure 1173) at a mass ratio of 100:2. Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, battery grade, moisture <20 ppm) was added, with a molar ratio of lithium salt to ionic liquid monomer of 1:10. The mixture was stirred for 2 hours in an argon atmosphere glove box (water and oxygen content <0.1 ppm) until completely dissolved, yielding a colorless and transparent solid electrolyte precursor solution.
[0029] The aforementioned core-shell structured magnetic conductive filler was added to the precursor solution, with a total filler mass fraction of 15% (based on the total mass of the solid electrolyte precursor solution). After ultrasonic dispersion for 30 minutes (ultrasonic power 300W, temperature controlled by an ice-water bath), it was transferred to a planetary ball mill, using zirconia balls as the grinding medium, a ball-to-material ratio of 10:1, a rotation speed of 400 rpm, and ball milling for 2 hours to obtain a uniform composite slurry. The slurry viscosity was tested using a rotational viscometer (Brookfield DV2T), and the viscosity at 25℃ was 8500 mPa·s, suitable for doctor blade coating processes.
[0030] S1.4 Selection Criteria for the Mass Fraction Range of Magnetic Conductive Filler The range of 8% to 25% in terms of mass fraction is based on the following: (1) When the mass fraction is less than 8%, the content of magnetic conductive filler in the solid electrolyte precursor solution is close to the percolation threshold of carbon nanotubes in the polymer matrix (about 5% to 10%), making it difficult to form a continuous conductive network, which leads to easy interruption of the conductive path during bending; at the same time, the magnetic responsiveness of the filler is insufficient, and the orientation efficiency under a magnetic field of 0.1T to 2T decreases significantly. The Hermans orientation factor is usually less than 0.3, and it is impossible to construct an effective anisotropic conductive structure. (2) When the mass fraction is higher than 25%, the rotational viscosity of the composite slurry increases sharply (usually exceeding 20,000 mPa·s), which exceeds the applicable viscosity range of the doctor blade coating process (generally requiring viscosity <15,000 mPa·s), resulting in uneven coating thickness and easy occurrence of bubbles and streaks; at the same time, the excessively high filler content will dilute the volume fraction of the ionic liquid monomer, reduce the continuity of the polymer ion transport matrix after curing, and lead to a decrease in ionic conductivity; (3) In Example 1, a mass fraction of 15% was used, at which point the slurry viscosity was 8500 mPa·s, suitable for doctor blade coating. Furthermore, the conductive network remained intact after curing, achieving an optimal balance between ionic conductivity and mechanical flexibility. Therefore, 8% to 25% is a reasonable window that balances the integrity of the conductive network, the efficiency of the magnetic field orientation, and the feasibility of the process. It should be noted that the above mass fraction is based on the total mass of the solid electrolyte precursor solution, and after curing and removal of volatile components, it corresponds to 8% to 25% of the total dry mass of the solid electrolyte layer.
[0031] S2. Coating and primary magnetic field orientation The composite slurry was coated onto the surface of a flexible polyethylene terephthalate (PET, 125 μm thick, corona-treated surface) substrate using an automatic doctor blade coating machine. The doctor blade gap was set to 200 μm, the coating speed to 50 mm / min, and the ambient temperature to 25℃ with relative humidity <30%. After coating, an electromagnet (pole diameter 10 cm, maximum field strength 2.5 T) was placed directly above the coating layer (5 cm from the coating surface) to apply a first steady magnetic field. H 1 is 1.0T, and the direction is parallel to the coating direction (defined as 0°, i.e., the x-axis direction), causing the magnetic conductive filler to be oriented along the first direction. The magnetic field is maintained for 10 minutes.
[0032] The orientation process of the coating under the action of a magnetic field was observed using an in-situ optical microscope (Olympus BX53M, equipped with a long working distance objective lens). It can be seen that the magnetic conductive filler begins to align along the direction of the magnetic field within 30 seconds after the magnetic field is applied, the orientation is basically stable after 5 minutes, and the orientation degree reaches a plateau after 10 minutes.
[0033] S3. Patterned photopolymerization Under the condition of maintaining a first steady magnetic field, the coating layer was patterned and cured with ultraviolet light. A periodic striped quartz glass mask (Cr mask, with alternating transparent and opaque areas) was used, with a stripe width of 200 μm and a stripe spacing of 400 μm (i.e., the center-to-center distance between adjacent transparent areas was 400 μm). The stripe direction was parallel to the direction of the first magnetic field (0°). The ultraviolet light source was a high-pressure mercury lamp (OmniCure S2000), with a main wavelength peak of 365 nm and a light intensity of 100 mW / cm². 2(Calibrated using an EIT UVICURE PLUSII UV energy meter), exposure time was 15 seconds.
[0034] Double bond conversion was monitored using real-time infrared spectroscopy (FTIR, Nicolet iS50, equipped with a diamond ATR accessory): In the cured region, the C=C stretching vibration peak (1635 cm⁻¹) was observed. -1 The intensity decreased by about 92%, indicating that the double bond conversion rate was about 92%; in the uncured region (shaded area), the double bond conversion rate was about 55%. The cured region forms a high-modulus region, and the uncured region forms a low-modulus precursor. The two are distributed alternately to form a curing gradient field.
[0035] The cross-sectional morphology of the patterned photocured region was observed using a scanning electron microscope (SEM, Hitachi SU8010). It was found that the interface between the high modulus region and the low modulus region was clear, with no obvious interdiffusion, and the width of the interface transition region was <10μm.
[0036] S4. Secondary magnetic field orientation Remove the first steady magnetic field, place a second electromagnet directly above the coating layer, and apply a second magnetic field. The direction of the second magnetic field forms a 90° angle with the first direction (i.e., the y-axis direction). The magnetic field strength is... H 2 is 0.4T ( H 2 / H (1=0.4), the application time is 3 minutes (0.3 times the first magnetic field application time). In the low modulus region, due to the high mobility of the polymer chain segments (double bond conversion rate is only 55%, crosslinking density is low), the magnetic conductive filler undergoes secondary orientation under the action of the second magnetic field, forming a second orientation arrangement at a 90° angle to the first orientation. In the high modulus region, because it is already highly cured (double bond conversion rate 92%), the chain segment movement is restricted, and the primary orientation is locked and remains unchanged.
[0037] Using a polarizing optical microscope (POM, Olympus BX51-P) with an analyzer rotation test, it was observed that the extinction direction in the high modulus region had an angle of 5° with the x-axis, and the extinction direction in the low modulus region had an angle of 88° with the x-axis, which is consistent with the XRD pole figure test results.
[0038] S4.1 Basis for selecting the time of application of the second magnetic field The application time of the second magnetic field in step S4 is 0.2 to 0.5 times the application time of the first magnetic field in step S2. This time range is selected based on the synergistic balance between magnetic torque-driven orientation dynamics and polymer chain segment relaxation behavior. (1) Constraint mechanism with a lower limit of 0.2 times: second magnetic field strength H 2 is only 0.3 to 0.7 times that of the first magnetic field (i.e., 0.3 to 1.4 T), and the magnetic torque τ = μ0·m× H2 (where m is the magnetic moment of the filler) decreases accordingly. If the application time is too short (<0.2 times), the rotational angular displacement of the magnetic conductive filler in the viscoelastic slurry in the low modulus region is insufficient to reach the thermodynamic equilibrium orientation state, and the Hermans orientation factor... f 2 is usually below 0.4, which leads to insufficient conductivity redundancy in the dual-orientation interlaced structure, and the complementary conduction effect decreases significantly when bending.
[0039] (2) Constraint mechanism of 0.5 times the upper limit: Although the high modulus region has been highly cured (double bond conversion rate > 90%), the long-term (> 0.5 times) weak magnetic field may still cause the following adverse effects: ① The filler at the interface between the high modulus region and the low modulus region undergoes slow rearrangement due to the relaxation of interface stress, which destroys the interface clarity of the primary orientation; ② The photoinitiator in the uncured region may undergo thermal decomposition pre-reaction under long-term room temperature exposure, which leads to an abnormal increase in the crosslinking density of the low modulus region during subsequent overall curing, and the modulus gradient is weakened; ③ Long-term magnetic field exposure increases the risk of magnetoagglomeration, especially fillers with high remanence (> 15 emu / g) may undergo magnetic dipole chain aggregation under weak field.
[0040] (3) Experimental verification of the optimal time window: In the system of Example 1, the first magnetic field was applied for 10 minutes and the second magnetic field was applied for 3 minutes (0.3 times). At this time, the orientation factor in the low modulus region was... f 2 reaches 0.58, and the orientation factor in the high modulus region is... f 1. No attenuation (maintained at 0.72), interface transition region width < 10 μm. If the second magnetic field application time exceeds 0.5 times (e.g., extended to 0.8 times or more), although the orientation factor in the low modulus region... f 2 may be slightly improved due to the continuous action of magnetic torque, but as mentioned earlier, the filler at the interface between the high-modulus and low-modulus regions will undergo slow rearrangement due to the long-term action of the weak magnetic field, resulting in a decrease in the primary orientation degree. 1 The decrease in modulus, the widening of the interface transition zone, and the thermal decomposition pre-reaction of the photoinitiator in the uncured region will cause an abnormally high crosslinking density in the low-modulus region, weakening the modulus gradient and ultimately leading to a decrease in bending durability. Therefore, considering both orientation kinetics and structural stability, a time ratio of 0.2 to 0.5 times is the key parameter for achieving the optimal balance between "effective secondary orientation" and "locked primary orientation".
[0041] S5. Overall curing The coating layer after secondary orientation was cured entirely by ultraviolet light, with the ultraviolet light source being an LED surface light source (365nm, light intensity 50mW / cm²). 2The curing temperature is 60℃ (about 40℃ lower than the exposure temperature during patterned photocuring, where the surface temperature of the coating layer is raised to about 100℃ due to the heat radiation of the mercury lamp during patterned photocuring), and the curing time is 5 minutes, so that the low modulus region is completely cured (double bond conversion rate is increased to >95%), resulting in a solid electrolyte layer with a thickness of about 180μm.
[0042] The glass transition temperature was determined by differential scanning calorimetry (DSC, TA Instruments Q2000, heating rate 10℃ / min, nitrogen atmosphere). The Tg in the high modulus region was 85℃, and the Tg in the low modulus region was 62℃, indicating that the crosslinking density of the two regions was significantly different.
[0043] The elastic modulus distribution of the solid electrolyte layer was tested using a nanoindenter (Bruker Hysitron TI 980) with a Berkovich diamond indenter. The test spacing was 50 μm, the test load was 1 mN, the loading rate was 100 μN / s, and the holding time was 2 seconds. The results showed that the elastic modulus of the high-modulus region was 2.8 ± 0.2 GPa, and the elastic modulus of the low-modulus region was 0.7 ± 0.1 GPa, with a ratio of 4.0. The spacing between adjacent high-modulus regions was 400 μm, consistent with the fringe spacing of the mask.
[0044] The orientation state was analyzed using X-ray diffraction pole figure analysis (XRD, Rigaku SmartLab, Cu Kα radiation, scanning range 2θ = 20°-30°, pole figure test step size 5°). In the high modulus region, the orientation direction of the magnetic conductive filler is at an angle of 5° to the coating direction (x-axis) (first orientation), while in the low modulus region, the angle is 88° (second orientation), resulting in a combined angle of 83° between the two orientations. Using Hermans orientation factors, the orientation factor f1 for the first orientation is 0.72, and the orientation factor for the second orientation is... f 2 = 0.58.
[0045] Cross-sectional samples were prepared and the morphology of the conductive network was observed using focused ion beam scanning electron microscopy (FIB-SEM, Helios G4 CX). It can be seen that in the high modulus region, carbon nanotubes are arranged parallel to the x-axis, forming a layered conductive pathway; in the low modulus region, carbon nanotubes are arranged along the y-axis, and are nearly orthogonal to the conductive pathway in the x-axis direction.
[0046] S6. Battery Assembly A lithium iron phosphate (LiFePO4, D50=2μm, specific capacity 160mAh / g) cathode slurry (active material: conductive carbon black:PVDF=8:1:1, solvent NMP, solid content 60%) was coated onto an aluminum foil (15μm thick), with a coating thickness of 100μm. The coating was then vacuum dried at 80℃ for 12 hours and rolled to obtain a cathode sheet (active material loading approximately 8mg / cm³). 2 ).
[0047] A graphite (D50=15μm, specific capacity 350mAh / g) negative electrode slurry (active material: conductive carbon black: SBR: CMC=95:1:2:2, solvent deionized water, solid content 50%) was coated onto a copper foil (thickness 10μm) to a thickness of 120μm. The coating was then vacuum dried at 80℃ for 12 hours and rolled to obtain a negative electrode sheet (active material loading approximately 6mg / cm³). 2 ).
[0048] The solid electrolyte layer was cut into 20mm×20mm squares and placed between the positive and negative electrode sheets. In an argon atmosphere glove box, it was hot-pressed and bonded at 80°C and 2MPa for 30 minutes to obtain a bendable solid flexible energy storage battery (designed capacity of about 5mAh).
[0049] Example 2
[0050] A first sublayer is prepared according to the steps of Example 1, wherein the patterned photocured stripes are oriented along the y-axis and perpendicular to the direction of the first stable magnetic field (x-axis); a second sublayer is prepared using a separate composite slurry, wherein the long axis of the patterned photocured stripes is oriented along the x-axis, the direction of the first magnetic field is parallel to the coating direction (x-axis), and the direction of the second magnetic field forms a 50° angle with the first direction (i.e., 50° with the x-axis). The long axis of the stripes in the first sublayer is perpendicular to the long axis of the stripes in the second sublayer.
[0051] The first sublayer and the second sublayer are stacked together, with the high-modulus region of the first sublayer and the low-modulus region of the second sublayer staggered in the thickness direction (i.e., the high-modulus region of the first sublayer corresponds to the low-modulus region of the second sublayer, and the low-modulus region of the first sublayer corresponds to the high-modulus region of the second sublayer). They are then hot-pressed together at 80°C and 1MPa for 10 minutes to obtain a bilayer solid electrolyte layer with a total thickness of approximately 360μm.
[0052] The elastic modulus distribution of the bilayer structure was tested using a nanoindenter. The elastic modulus of the high-modulus region in the first sublayer was 2.6 ± 0.2 GPa, and that of the low-modulus region was 0.6 ± 0.1 GPa, with a modulus ratio of 4.3. In the second sublayer, the high-modulus region was 2.9 ± 0.2 GPa, and that of the low-modulus region was 0.8 ± 0.1 GPa, with a modulus ratio of 3.6. X-ray diffraction pole figure analysis showed that the orientation angle between the high-modulus region and the thickness direction (z-axis) in the first sublayer was 8°, and that in the low-modulus region was 92°. In the second sublayer, the orientation angle between the high-modulus region and the thickness direction was 85°, and that in the low-modulus region was 28°.
[0053] Following the battery assembly steps of Example 1, an orthogonal bilayer is used as the solid electrolyte layer to assemble a bendable solid flexible energy storage battery.
[0054] Example 3
[0055] In the composite slurry preparation step of Example 1, a non-magnetic ionic conductor filler Li was additionally added. 1.3 Al 0.3 Ti 1.7 (PO4)3 (LATP, D50 = 300 nm, ionic conductivity 1.2 × 10⁻⁶) -3 The mass ratio of LATP to magnetic conductive filler was 1:1 (S / cm, room temperature), and the ball milling time was extended to 3 hours (400 rpm) to ensure that the two fillers were uniformly dispersed and interleaved.
[0056] The microstructure of the composite slurry after drying was observed using transmission electron microscopy. It was found that LATP nanoparticles were uniformly dispersed between the magnetic conductive fillers, and no obvious agglomeration occurred between the two, forming an interwoven microstructure.
[0057] The remaining steps are the same as in Example 1.
[0058] The ionic conductivity of the solid electrolyte layer was measured using electrochemical impedance spectroscopy (EIS, Bio-Logic VMP-300, frequency range 1 Hz to 1 MHz, amplitude 10 mV, room temperature) with a blocked electrode (stainless steel / electrolyte / stainless steel symmetric cell). The results showed that the ionic conductivity of the LATP-containing solid electrolyte layer was 8.5 × 10⁻⁶. -5 S / cm, higher than the control sample without LATP (3.5 × 10⁻⁶). -5 The conductivity (S / cm) is approximately 2.4 times higher. This increase in conductivity is attributed to the structure in which the continuous ion transport channels formed by the interleaved distribution of non-magnetic ion-conducting fillers and magnetic conductive fillers are interleaved with the in-plane electronic conductive network. LATP provides additional lithium-ion transport paths and works synergistically with the magnetic conductive fillers to construct a continuous ion conduction network.
[0059] Scanning electron microscopy was used to observe the cross-sectional morphology of the LATP-containing solid electrolyte layer. It was found that LATP particles filled the gaps in the magnetic conductive filler network, forming an "ion bridge" structure, which shortened the detour path of lithium ion transport.
[0060] Example 4
[0061] Prepared according to the steps of Example 1, the difference being that in step S4, the direction of the second magnetic field forms a 60° angle with the first direction (instead of 90°), and the magnetic field strength... H 2 is 0.5T ( H 2 / H 1=0.5), and the application time is 4 minutes.
[0062] X-ray diffraction pole figure analysis showed that the orientation direction of the magnetic conductive filler in the high modulus region was 4° with the coating direction (first orientation), and the orientation direction in the low modulus region was 62° with the coating direction (second orientation). The angle between the two orientations was 58° (close to the lower limit of 50°).
[0063] Using a nanoindenter, the elastic modulus in the high modulus region was 2.7 GPa, and the elastic modulus in the low modulus region was 0.9 GPa, with a ratio of 3.0.
[0064] Assemble the battery according to the battery assembly steps in Example 1.
[0065] Example 5
[0066] Prepared according to the steps of Example 1, except that: in step S3, the patterning photocuring uses a mask with a stripe width of 100 μm and a stripe spacing of 200 μm, and the ultraviolet light intensity is 150 mW / cm². 2 The exposure time is 25 seconds, resulting in a double bond conversion rate of approximately 96% in the cured region and approximately 35% in the uncured region. In step S4, the direction of the second magnetic field forms a 120° angle with the first direction, and the magnetic field strength is... H 2 is 0.6T ( H 2 / H 1=0.6), and the application time is 5 minutes.
[0067] X-ray diffraction pole figure analysis showed that the orientation direction of the magnetic conductive filler in the high modulus region was 3° with the coating direction (first orientation), and the orientation direction in the low modulus region was 118° with the coating direction (second orientation). The angle between the two orientations was 115° (close to 120°).
[0068] Using a nanoindenter, the elastic modulus in the high modulus region was 3.5 GPa, and the elastic modulus in the low modulus region was 0.35 GPa, with a ratio of 10.0.
[0069] Assemble the battery according to the battery assembly steps in Example 1.
[0070] Example 6
[0071] Prepared according to the steps of Example 1, except that: in step S3, the patterning photocuring uses a mask with a stripe width of 500 μm and a stripe spacing of 1000 μm, and the ultraviolet light intensity is 80 mW / cm². 2 The exposure time is 10 seconds, resulting in a double bond conversion rate of approximately 85% in the cured region and approximately 60% in the uncured region. In step S4, the direction of the second magnetic field forms a 90° angle with the first direction, and the magnetic field strength is... H 2 is 0.3T ( H 2 / H 1=0.3), and the application time is 2 minutes.
[0072] X-ray diffraction pole figure analysis showed that the orientation direction of the magnetic conductive filler in the high modulus region was 6° with the coating direction (first orientation), and the orientation direction in the low modulus region was 89° with the coating direction (second orientation), with a total angle of 83° between the two orientations.
[0073] The elastic modulus was measured using a nanoindenter. The elastic modulus in the high modulus region was 1.8 GPa, and the elastic modulus in the low modulus region was 0.9 GPa. The ratio of the elastic moduli was 2.0.
[0074] Assemble the battery according to the battery assembly steps in Example 1.
[0075] Comparative Example 1 Prepared according to Example 1, but omitting the first magnetic field orientation (S2) and second magnetic field orientation (S4) steps, the composite slurry was directly patterned and cured under magnetic field-free conditions after coating.
[0076] X-ray diffraction pole figure analysis showed no obvious orientation peaks, indicating that the filler was isotropically distributed in the solid electrolyte layer.
[0077] The elastic modulus of the high modulus region was 1.5±0.2 GPa and that of the low modulus region was 1.3±0.2 GPa, with a modulus ratio of only 1.2. This indicates that the crosslinking density difference between the high modulus region and the low modulus region is small under magnetic field conditions. This may be because the physical barrier effect of the non-oriented filler enhances the scattering of ultraviolet light, resulting in partial photocuring in the uncured area.
[0078] SEM observation of the cross-sectional morphology revealed that the filler material was randomly entangled and distributed without any directional arrangement.
[0079] Comparative Example 2 Prepared according to Example 1, but omitting the secondary magnetic field orientation step (S4) and retaining only the primary magnetic field orientation step (S2), with the remaining steps being exactly the same as in Example 1.
[0080] X-ray diffraction pole figure analysis revealed only a single orientation peak in the solid electrolyte layer, with the orientation direction at an angle of 6° to the coating direction. The Hermans orientation factor was [not specified]. f =0.75, indicating that the first orientation was effective.
[0081] The elastic modulus of the high modulus region was 2.5±0.2 GPa and that of the low modulus region was 0.9±0.1 GPa, with a modulus ratio of 2.8, as measured by a nanoindenter.
[0082] SEM observation of the cross-sectional morphology revealed that the filler in the high modulus region was oriented along the x-axis, but the filler in the low modulus region, having not undergone secondary orientation, experienced partial relaxation after the removal of the magnetic field, resulting in a near-random distribution.
[0083] Comparative Example 3 The core-shell magnetic conductive filler of Example 1 was replaced with multi-walled carbon nanotubes (without Fe3O4 core, outer diameter 10-20nm, length 5-15μm, same as the carbon nanotubes used in Example 1), and the remaining steps were the same as in Example 1.
[0084] Since pure multi-walled carbon nanotubes are diamagnetic materials (magnetic susceptibility χ≈-3.5×10⁻⁶), -6 The magnetization is extremely low (M=χH≈-1.4×10⁻⁶ emu / g·Oe) under a magnetic field of 0.4T (emu / g·Oe). -6 The carbon nanotubes (emu / g) could not generate an effective magnetic torque to orient them. X-ray diffraction pole figure analysis did not observe any obvious orientation peaks, and the filler in the solid electrolyte layer was randomly distributed.
[0085] Using a vibrating sample magnetometer, the filler showed no coercivity or remanence, and its saturation magnetization was close to zero (<0.01 emu / g).
[0086] The elastic modulus of the high modulus region was 2.7±0.2 GPa and that of the low modulus region was 0.8±0.1 GPa, with a modulus ratio of 3.4, as measured by a nanoindenter.
[0087] SEM observation of the cross-sectional morphology revealed that the carbon nanotubes formed a randomly entangled network with no directional arrangement.
[0088] Comparative Example 4 The composite slurry was prepared according to step S1 of Example 1 and coated onto the surface of the PET substrate. A first steady magnetic field was applied during the coating process. H 1 = 1.0T, direction 0°), maintain for 10 minutes to orient the magnetic conductive filler along the first direction.
[0089] Remove the first steady magnetic field and immediately apply the second magnetic field. H2=0.4T, direction 90°), maintain for 3 minutes to cause secondary orientation of the magnetic conductive filler.
[0090] Subsequently, the coating layer was cured entirely under ultraviolet light (without using a patterned mask, directly using light at an intensity of 100mW / cm²). 2 The solid electrolyte layer with no modulus gradient was obtained by uniform ultraviolet light irradiation, curing temperature of 60℃ and curing time of 10 minutes.
[0091] X-ray diffraction pole figure analysis revealed two orientation peaks in the solid electrolyte layer. The first orientation direction had an angle of 7° with the coating direction, and the second orientation direction had an angle of 86° with the coating direction. The combined angle between the two orientations was 79°. The Hermans orientation factors were... f 1 = 0.70 and f 2 = 0.55, indicating that both magnetic field orientations were effective.
[0092] The elastic modulus distribution was tested using a nanoindenter with a test spacing of 50 μm and a test load of 1 mN. The results showed that the elastic modulus of the electrolyte layer was uniform, approximately 1.6 ± 0.1 GPa, with no obvious distinction between high and low modulus regions.
[0093] SEM observation of the cross-sectional morphology revealed the presence of a dual-orientation structure, but the elastic modulus of the entire cross-section was uniform, with no alternating soft and hard regions.
[0094] Comparative Example 5 Prepared according to Example 1, but omitting the primary magnetic field orientation (S2) and secondary magnetic field orientation (S4) steps, the composite slurry was directly patterned and cured by photocuring under magnetic field-free conditions after coating. Other process parameters (mask stripe width 200 μm, spacing 400 μm, light intensity 100 mW / cm²) 2 The process (exposure for 15 seconds, overall curing at 60°C for 5 minutes) is exactly the same as in Example 1.
[0095] X-ray diffraction pole figure analysis revealed no obvious orientation peaks, indicating that the filler material was randomly distributed.
[0096] The elastic modulus of the high modulus region was 2.4±0.2GPa and that of the low modulus region was 0.6±0.1GPa, with a modulus ratio of 4.0, which is similar to the modulus ratio (4.0) of Example 1. This indicates that the patterned photocuring process itself is not affected by the magnetic field orientation.
[0097] SEM observation of the cross-sectional morphology revealed a clear alternation between high-modulus and low-modulus regions, but the filler was randomly distributed in both regions.
[0098] II. Performance Testing The batteries prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to the following system tests: 1. Bending performance test The battery was fixed on a bending tester with a bending radius of 1 mm (corresponding to approximately 10% of the maximum strain on the battery surface) and a bending frequency of 1 Hz (i.e., one 180° bend-recovery cycle per second), for a total of 10,000 cycles. It should be noted that this bending radius represents an extreme and stringent test condition, designed to fully expose structural stability defects in the electrolyte layer under extreme deformation. Typical bending radii for actual wearable devices are usually 5–10 mm (approximately 1–2% strain), and battery performance under these normal conditions will be better than the extreme test results.
[0099] During the bending test, the test was paused after every 1000 cycles. The battery was removed from the bending fixture and allowed to stand for 30 minutes to return to room temperature. First, a visual inspection was performed to check for through-cracks on the electrolyte layer surface and for delamination or detachment of the electrodes. Then, the battery was re-clamped and subjected to a constant current charge-discharge test at 0.1C (voltage range 2.5-4.2V), and the discharge capacity was recorded. Simultaneously, during the bending cycle, a four-probe method was used to monitor the change in the battery's in-situ surface resistance. The probes were connected to the electrochemical workstation via flexible wires, and resistance values were collected every 500 cycles to monitor the changing trend of the conductive network integrity.
[0100] For Comparative Example 2 (single orientation), an additional orientation dependence test was conducted: the battery was bent in two ways, with the orientation direction parallel to the bending axis (0° bend) and the orientation direction perpendicular to the bending axis (90° bend), with other test conditions remaining the same.
[0101] For Example 1, an additional 45° bending test was performed (the bending axis is at 45° to the x-axis) to verify the stability of the dual-orientation structure in the non-principal axis direction.
[0102] All tests were conducted in a constant temperature and humidity environment (25±1℃, relative humidity 45±5%). Five samples were tested in each group, and the average value was taken. The error is expressed as standard deviation. The standard deviation of capacity retention rate of Examples 1-6 and each comparative example was controlled within ±2%~±5%, with good reproducibility. This was mainly due to: (1) the composite slurry was prepared by an automatic doctor blade coating machine with a coating thickness accuracy of ±5μm; (2) the magnetic field strength was calibrated in real time by a gaussmeter with fluctuation <±0.02T; (3) the patterned photocuring used a quartz glass Cr mask with a stripe size accuracy of ±2μm; and (4) the battery assembly used a hot-press composite process with a pressure accuracy of ±0.05MPa. The above automation and precise control ensured the high consistency of samples within the batch.
[0103] Table 1. Performance of each embodiment and comparative example after 10,000 cyclic bends under conditions of a bending radius of 1 mm and a frequency of 1 Hz.
[0104] Based on the 1mm ultimate bending test data and the physical laws of strain-damage, it can be deduced that under a larger bending radius (smaller strain), the capacity retention rate of each sample will show an upward trend, and the advantages of Example 1 will still be maintained.
[0105] 2. Real-time monitoring of the rate of change of resistance in different bending directions The in-situ change in in-plane resistivity of a solid electrolyte layer during bending was monitored using a four-probe method. The solid electrolyte layer was cut into 10mm × 50mm strips, and four probes (5mm apart) were evenly spaced on the sample surface. The probes were connected to an electrochemical workstation (Bio-Logic VMP-300) via flexible wires. One end of the sample was fixed, and the other end was connected to a displacement control mechanism to achieve controlled bending.
[0106] A constant DC current of 1mA is applied, and the voltage drop during the bending process is recorded in real time. The in-plane resistance is calculated according to Ohm's law. The bending radius is set to 1mm, and the bending angle cycles from 0° to 180° and back to 0°. The rate of change of resistance is calculated as ΔR / R0×100%, where R0 is the initial resistance and ΔR is the resistance increment during the bending process.
[0107] For Example 1 and Comparative Example 2, the rate of change of resistance was tested when the bending axis was at 0°, 45° and 90° to the x-axis, respectively.
[0108] Table 2. Rate of resistance change under different bending directions (after 10,000 bends)
[0109] 3. Elastic modulus distribution test The elastic modulus distribution of the solid electrolyte layer in each sample was tested using a nanoindenter (Bruker Hysitron TI 980). A Berkovich diamond indenter was used, with a test load of 1 mN, a loading rate of 100 μN / s, a holding time of 2 seconds, and a test spacing of 100 μm. The test was conducted in a gridded area of 1 mm × 1 mm (100 test points in total). The elastic modulus of each test point was calculated using the Oliver-Pharr method, and the modulus distribution was plotted.
[0110] Table 3 Elastic modulus distribution of solid electrolyte layers in each embodiment and comparative example
[0111] 4. Orientation analysis test The orientation of the magnetically conductive filler in the solid electrolyte layer of each sample was determined by X-ray diffraction pole figure analysis (XRD, Rigaku SmartLab, Cu Kα radiation, λ=1.5406Å). Transmission geometry was used, with a sample thickness of approximately 180 μm and an X-ray beam size of 0.5 mm × 0.5 mm. Pole figure scanning was performed at 2θ=26° (carbon nanotube (002) crystal plane), with a pole angle χ ranging from 0° to 90° in 5° increments and an azimuth angle φ ranging from 0° to 360° in 5° increments. Hermans orientation factor was used. f Quantitative description of orientation degree f =1 indicates complete orientation. f =0 indicates a random distribution. f =-0.5 indicates that the orientation is completely perpendicular to the reference direction.
[0112] Table 4 Orientation state of magnetic conductive filler in solid electrolyte layer of each embodiment and comparative example
[0113] 5. Microscopic morphological observation before and after bending The changes in the cross-sectional microstructure of the solid electrolyte layers of Example 1 and Comparative Example 2 before and after 10,000 bending cycles were observed using focused ion beam scanning electron microscopy (FIB-SEM, Thermo Fisher Helios G4 CX). After the samples were subjected to liquid nitrogen embrittlement, gold (approximately 5 nm thick) was sputtered onto the cross-sectional surface for SEM observation.
[0114] Example 1, before bending: In the high-modulus region, carbon nanotubes are arranged parallel to each other along the x-axis, with a clear layered structure; in the low-modulus region, carbon nanotubes are arranged along the y-axis, and the conductive pathways are nearly orthogonal to the x-axis. The interface between the high-modulus and low-modulus regions is clear, with no obvious defects.
[0115] After 10,000 bending cycles in Example 1: the orientation of carbon nanotubes in the high-modulus region remained basically unchanged, with no obvious breakage observed; the orientation of carbon nanotubes in the low-modulus region fluctuated slightly, but the overall network structure remained intact, with no large-area breakage observed. Slight shear deformation occurred at the interface between the high-modulus and low-modulus regions, but no debonding or cracking occurred.
[0116] Comparative Example 2 (0° bend): Before bending: In the high modulus region, carbon nanotubes are oriented along the x-axis, while in the low modulus region, carbon nanotubes are randomly distributed.
[0117] Comparative Example 2 (0° bend): After 10,000 bends, the orientation of carbon nanotubes in the high modulus region remained relatively good, but in the low modulus region, due to the lack of conductive redundancy for secondary orientation, some areas showed conductive network breaks and voids.
[0118] Comparative Example 2 (90° bend): After 10,000 bends, carbon nanotubes oriented along the x-axis in the high modulus region are stretched vertically, resulting in large-area fractures and pull-outs, and severe damage to the conductive network; carbon nanotubes randomly distributed in the low modulus region cannot provide effective conductivity compensation, and through-cracks are visible in the cross-section.
[0119] III. Results Analysis The system test results of the above embodiments and comparative experiments lead to the following key conclusions: Example 1 exhibits capacitance retention of 91%, 89%, and 90% at 0°, 45°, and 90° bending directions, respectively, with resistance changes of 12%, 15%, and 13%. The anisotropy coefficient (maximum resistance change rate / minimum resistance change rate) is only 1.25, indicating that the dual-orientation staggered structure maintains excellent conductivity stability across different bending directions. In contrast, Comparative Example 2 (single orientation) demonstrates strong orientation dependence: when bent along the orientation direction (0°), the capacitance retention is 61%, and the resistance change rate is 180%; however, when bent perpendicular to the orientation direction (90°), the capacitance retention drops sharply to 38%, and the resistance change rate reaches a high of 420%. The anisotropy coefficient is 2.33, indicating significant performance differences in different directions for the single-orientation structure.
[0120] This result directly demonstrates a serious flaw in the existing design approach that pursues optimal conductivity in a single direction—under bending perpendicular to the orientation direction, the conductive path in a single orientation is stretched and broken, and there is no conductive redundancy in other directions to compensate. This invention overcomes this technical bias by constructing a dual-orientation staggered structure, achieving conductive stability under multi-directional bending.
[0121] Example 1 (bi-orientation + modulus gradient, modulus ratio 4.0) has a capacitance retention of 91% and a resistivity change of 12%.
[0122] Comparative Example 4 (bi-orientation but no modulus gradient) successfully constructed a bi-orientation structure (the angle between the two orientations is 79°, and the orientation factor is...) through two magnetic field orientations. f 1 = 0.70 fComparative Example 5 (with modulus gradient but no magnetic field orientation) has a modulus ratio similar to that of Example 1 (4.0), but due to the lack of a modulus gradient formed by patterned photocuring, the elastic modulus of the entire electrolyte layer is uniform (approximately 1.6 GPa). During bending, stress cannot be effectively dispersed, and high-strain areas directly act on the cured dual-oriented conductive network, leading to large-area breakage of the conductive pathways. Its capacity retention rate is only 55%, and its resistance change rate is 150%, far worse than Example 1. Comparative Example 5 (with modulus gradient but no magnetic field orientation) has a modulus ratio similar to that of Example 1, but due to the random distribution of conductive fillers, it cannot form effective directional conductive pathways. During bending, the contact resistance between the fillers fluctuates randomly and cannot be compensated for by orientation design. Its capacity retention rate is 52%, and its resistance change rate is 280%, also far worse than Example 1.
[0123] The above comparison shows that both the dual-orientation structure and the modulus gradient are indispensable; neither can achieve the technical effect of Example 1 when they exist alone. Only when the dual-orientation staggered structure and the modulus gradient of 2:1 to 10:1 work synergistically can excellent bending stability be achieved through the mechanical division of labor of the "rigid skeleton-flexible hinge" and the electrical complementarity of the multi-directional conductive paths. This synergistic effect is something that those skilled in the art cannot directly anticipate from the prior art.
[0124] To further eliminate the interference of differences in preparation methods on the conclusions, the following cross-comparison of three sets of comparative examples verifies the irreplaceability of the synergistic effect: (1) Comparative Example 2 (single orientation + modulus gradient) vs Example 1 (dual orientation + modulus gradient): Both have the same modulus gradient structure (modulus ratios of 2.8 and 4.0, respectively), but the conductive networks are single-oriented and dual-oriented, respectively. Comparative Example 2 has a capacity retention of only 61% in the optimal bending direction (0°) and exhibits strong orientation dependence (dropping sharply to 38% when bent at 90°); while Example 1 maintains approximately 91% in all directions. This indicates that, given the presence of a modulus gradient, a dual-oriented staggered structure is a necessary condition for eliminating orientation dependence and achieving stable conduction in multiple directions.
[0125] (2) Comparative Example 5 (non-oriented + modulus gradient) vs Example 1 (bi-oriented + modulus gradient): Both have similar modulus gradients (modulus ratio 4.0), but their conductive networks are randomly distributed and bi-oriented, respectively. Comparative Example 5 has a capacitance retention rate of only 52% and a resistance change rate of 280%. This shows that, given the presence of a modulus gradient, the non-oriented random conductive network cannot maintain an effective conductive path under bending, and the bi-oriented design is indispensable.
[0126] (3) Comparative Example 4 (bi-orientation + no modulus gradient) vs Example 1 (bi-orientation + modulus gradient): The degree of bi-orientation of Comparative Example 4 ( f 1 = 0.70f 2=0.55) and Example 1 ( f 1 = 0.72, f The high similarity (2=0.58) indicates that its conductive network structure has been fully established. However, the capacity retention rate is only 55%, far lower than the 91% of Example 1. Although Comparative Example 4 uses monolithic curing (unpatterned photocuring) with a uniform crosslinking density distribution, this homogeneous curing itself does not lead to conductive network breakage; on the contrary, the stress of the homogeneous structure is concentrated in the high strain region when bent, lacking deformation buffer in the low modulus region, causing the cured bi-oriented conductive network to directly bear tensile stress and break. Therefore, the performance difference can be attributed to the lack of modulus gradient.
[0127] In summary, the above triangular comparisons show that modulus gradient alone (Comparative Example 5, 52%), dual orientation alone (Comparative Example 4, 55%), and modulus gradient plus single orientation (Comparative Example 2, average ~50%) all fail to achieve the technical effect of Example 1 (91%). Only when the dual-orientation staggered structure and the modulus gradient of 2:1 to 10:1 are synergistically constructed within the same electrolyte layer can an unexpected performance leap be achieved through "mechanical division of labor - electrical complementarity". It should be further noted that the overall curing conditions of Comparative Example 4 (light intensity 100mW / cm²) 2 After overall curing (at 60°C and 10 minutes) and in Example 1, the double bond conversion rate of Comparative Example 4 was >95%, and the degree of crosslinking was comparable. The essential difference between the two lies only in the lack of a spatial crosslinking density gradient caused by patterned photocuring in Comparative Example 4, rather than insufficient curing degree. Therefore, the performance difference between Comparative Example 4 and Example 1 can be attributed to the presence or absence of a modulus gradient, rather than the difference in curing process.
[0128] Example 4 (orientation angle 58°, close to the lower limit of 50°) exhibited a capacitance retention of 88% and a resistance change of 16%, slightly lower than Example 1 (90° angle), but still significantly better than all comparative examples, demonstrating that this angle provides effective conductivity redundancy. Example 5 (orientation angle 115°, close to the upper limit of 120°; modulus ratio 10:1) showed a capacitance retention of 85% and a resistance change of 18%. Although the low-modulus region becomes too soft when the modulus ratio reaches the upper limit, potentially leading to excessive local deformation, the dual-orientation structure still provides basic conductivity redundancy, outperforming the comparative examples. Example 6 (modulus ratio 2:1 lower limit) showed a capacitance retention of 87% and a resistance change of 17%. When the modulus ratio approaches the lower limit, the mechanical difference between the high-modulus and low-modulus regions decreases, weakening the deformation zoning effect, but the dual-orientation structure still functions.
[0129] The above-described parameter variation examples demonstrate that the technical effects of the present invention can be achieved within the orientation angle range of 50°-120° and the modulus ratio range of 2:1 to 10:1. Furthermore, the performance changes gradually within this range, indicating that the parameter selection has reasonable process tolerance.
[0130] Compared to Comparative Example 3 (non-magnetic carbon nanotubes), Example 1 showed a significantly reduced performance degradation after bending (capacity retention 91% vs 45%, resistivity change 12% vs 400%). Although Comparative Example 3 had a similar modulus gradient structure (modulus ratio 3.4), the pure carbon nanotubes, being diamagnetic, could not achieve effective orientation under a 0.4T magnetic field, and the random distribution of the filler led to rapid deterioration of the conductive network under bending. This demonstrates the irreplaceable role of core-shell magnetic conductive fillers in achieving low-field orientation and constructing controllable anisotropic conductive networks.
[0131] Compared to Example 1, Example 2 further improved capacitance retention and electrical stability (93% vs 91%, 10% vs 12%), demonstrating that the orthogonal bilayer design effectively dispersed multi-directional stress. Nanoindentation testing showed that the two layers had consistent modulus distribution, and hot-pressing did not disrupt their respective spatial non-uniform structures. The first sublayer (oriented parallel to the thickness direction) mainly bears the stress dispersion in the thickness direction, while the second sublayer (oriented perpendicular to the thickness direction) mainly bears the stress dispersion in the in-plane direction. The orthogonal synergy between the two layers suppressed interlayer stress concentration and delamination.
[0132] Example 3 showed the lowest rate of change in resistance (8%) compared to Example 1. AC impedance testing confirmed that the addition of LATP increased ionic conductivity (8.5 × 10⁻⁶). -5 S / cm vs 3.5×10 -5 S / cm, an increase of approximately 2.4 times. Notably, the capacity retention rate of Example 3 (94%) was slightly higher than that of Example 1 (91%), indicating that efficient ion transport helps reduce electrode polarization and indirectly improves electrochemical stability during bending. The structure, in which the continuous ion transport channels formed by the interleaved distribution of LATP and magnetic conductive filler and the in-plane electronic conductive network are interleaved, maintains high ion transport efficiency during bending.
[0133] In summary, this invention overcomes the technical bias of pursuing optimal conductivity in a single direction in existing technologies by synergistically designing a spatially non-uniform solidification structure, a bi-oriented staggered arrangement, and a non-magnetic ionic conductor filler. This enables the long-term maintenance of the conductive network integrity of solid-state flexible energy storage batteries under multi-directional bending conditions. The synergistic effect of the bi-oriented structure and modulus gradient produces unexpected technical effects: neither bi-oriented structure alone (without modulus gradient) nor modulus gradient alone (without orientation) can achieve the performance level when both are combined. This synergistic effect provides a new technical path for the structural design of flexible solid-state batteries.
Claims
1. A flexible solid-state energy storage battery with embedded magnetic conductive filler, characterized in that, include: A positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode; The solid electrolyte layer contains embedded magnetic conductive filler, which forms a conductive network in the solid electrolyte layer. The conductive network is covered and isolated by the solid electrolyte matrix and is discontinuous in the battery thickness direction to maintain the electronic insulation of the solid electrolyte layer. The solid electrolyte layer has high-modulus regions and low-modulus regions arranged in an alternating stripe pattern, and the ratio of the elastic modulus of the high-modulus region to the low-modulus region is 2:1 to 10:
1. The magnetic conductive filler in the high modulus region is arranged in a first orientation, and the magnetic conductive filler in the low modulus region is arranged in a second orientation, with the first orientation and the second orientation forming an angle of 50° to 120°. The high-modulus region and the low-modulus region respectively assume the functions of structural support and deformation absorption when the battery is bent. The staggered arrangement of the first orientation and the second orientation enables the conductive network to maintain the continuity of conductive pathways in at least two different directions in the plane.
2. The bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 1, characterized in that, The magnetic conductive filler includes a core-shell structure, which includes a magnetic core and a conductive shell covering the surface of the magnetic core; the coercivity of the magnetic core is 50 Oe to 500 Oe, and the remanence is 5 emu / g to 20 emu / g.
3. The bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 1, characterized in that, In the high modulus region, the mass fraction of the magnetic conductive filler is higher than that in the low modulus region, and the total mass fraction of the magnetic conductive filler in the solid electrolyte layer is 8% to 25%.
4. A bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 1, characterized in that, The solid electrolyte layer includes a first sublayer near the positive electrode and a second sublayer near the negative electrode; the high modulus region and the low modulus region in the first sublayer are arranged in an alternating stripe pattern, and the stripes extend along the in-plane direction of the first plane; the high modulus region and the low modulus region in the second sublayer are arranged in an alternating stripe pattern, and the stripes extend along the in-plane direction of the second plane, and the in-plane direction of the first plane and the in-plane direction of the second plane are perpendicular to each other.
5. A bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 1, characterized in that, The solid electrolyte layer also includes a non-magnetic ion conductor filler, which is interspersed with the magnetic conductive filler to form a structure in which continuous ion transport channels and in-plane electronic conductive networks are interspersed; wherein, the mass ratio of the non-magnetic ion conductor filler to the magnetic conductive filler is 1:3 to 3:1, and the ionic conductivity of the solid electrolyte layer is 1.5 to 5 times higher than that of the control sample without the non-magnetic ion conductor filler; the in-plane electronic conductive network is covered and isolated by the solid electrolyte matrix and is discontinuous in the thickness direction of the battery.
6. A method for preparing a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler as described in any one of claims 1 to 5, characterized in that, include: S1: Magnetic conductive filler is dispersed in a solid electrolyte precursor solution containing photocurable monomers to obtain a composite slurry; S2: The composite slurry is coated onto the surface of a flexible substrate. During the coating process, a first steady magnetic field is applied, with a magnetic field strength of... H 1 is 0.1T to 2T, and the direction of the first steady magnetic field is parallel to the coating direction, so that the magnetic conductive filler is oriented along the first direction; S3: Under the condition of maintaining the first steady magnetic field, the coating layer is subjected to patterned photocuring. The patterned photocuring adopts a periodic stripe pattern with a stripe width of 50μm to 500μm and a stripe spacing of 100μm to 1000μm, so that a curing gradient field with alternating cured and uncured areas is formed in the coating layer; wherein, the cured area corresponds to the formation of the high modulus region, and the uncured area forms the low modulus region after overall curing in step S5; S4: Remove the first steady magnetic field and apply a second magnetic field, the direction of which makes an angle of 50° to 120° with the first direction, the magnetic field strength... H 2 and the strength of the first magnetic field H The ratio of 1 is H 2 / H 1 = 0.3 to 0.7, causing the magnetic conductive filler in the uncured area to undergo secondary orientation, while the primary orientation in the cured area is locked, forming an interleaved orientation structure; S5: The coating layer after secondary orientation is cured as a whole. The temperature of the overall curing is lower than the surface temperature of the coating layer during patterning photocuring in step S3. The uncured area is cross-linked and cured to form the low modulus region. The ratio of the elastic modulus of the high modulus region to the low modulus region is 2:1 to 10:1, thus obtaining the solid electrolyte layer.
7. The method for preparing a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 6, characterized in that, In step S3, the double bond conversion rate of the cured region is more than 30 percentage points higher than that of the uncured region, and after overall curing in step S5, the glass transition temperature of the high modulus region is more than 15°C higher than that of the low modulus region.
8. The method for preparing a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 6, characterized in that, The photocurable monomer in step S1 includes an ionic liquid monomer containing double bonds, which forms the ion transport matrix of the solid electrolyte layer after photocuring.
9. The method for preparing a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 6, characterized in that, In step S4, the application time of the second magnetic field is 0.2 to 0.5 times that of the application time of the first magnetic field in step S2.
10. The method for preparing a bendable solid-state flexible energy storage battery with embedded magnetic conductive filler according to claim 6, characterized in that, In step S3, the stripe direction of the patterned photocuring is parallel or perpendicular to the direction of the first steady magnetic field.
